Formulasi Model Knowledge Management Pendukung Kolaborasi Desain Infrastruktur Berkelanjutan - Rahmawati, Yani; Utomo, Christiono (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
Economic, social, and environment are three main aspects that support the achievement of sustainable infrastructure development. Practically, those three aspects often found to be unintegrated in design. Collaborative design can be applied in multi-disciplines participants of design process to produce best design as integrated solution in realizing sustainable infrastructure development. Knowledge Management (KM) found to be essential for successful collaborative design. This reseach aims to develop concept of spatial configuration and economic value on adaptive and collaborative of sustainable infrastructure development. This research is conducted based on requirements in developing conceptual approach to direct the design process, with specific target to develop collaborative design through the application of supporting model in the form of correlation patterns between adaptive and collaborative variables. Literature study and Structural Equation Modeling (SEM) is applied to formulate the model of KM, and it is confirmed that KM has important role in supporting successful collaborative design